Population dynamics of Chrysomya megacephala (Diptera: Calliphoridae) at different temperatures - Silva, I. C.R.; Godoy, W. A.C. [UNESP]; Von Zuben, C. J. [UNESP]; Mancera, P. F.A. [UNESP] (My University, 2004)
In this study we analysed the theoretical population dynamics of C. megacephala, an exotic blowfly, kept at 25 and 30°C, using a density-dependent mathematical model, with parametric estimates of survival and fecundity in the laboratory. No change in terms of oscillation patterns was found for the two temperatures. The populations exhibited a two-point limit cycle, i.e. oscillations between two fixed points, at 25 and 30°C. However, a quantitative change was observed, indicating that at 25°C the number of immatures in equilibrium is 1176 and at 30°C, 1944. The implications of this difference in terms of equilibrium for population dynamics of C. megacephala are discussed.
Keywords: Chrysomya megacephala; Competition; Mathematical model; Population dynamics; Temperatures